Effectiveness of Implementing Inclusive Education: Challenges and Opportunities in Culturally Diverse Classrooms - A. Erni Ratna Dewi (Journal of Pedagogi, 2024)
Inclusive education has become a major focus in the global context to ensure equal access to education for all students, including those with special needs or from diverse cultural backgrounds. The purpose of this study is to evaluate the effectiveness of implementing inclusive education in culturally diverse classrooms, identify the challenges faced and explore the opportunities that exist. The methods used in this study involved a literature review and case analysis to understand the implementation of inclusive education and its impact on students' learning quality and social development. The results show that inclusive education improves learning quality and develops students' social skills and empathy. However, some key challenges were identified including a lack of teacher understanding and training, limited resources and social and cultural barriers. The implications of this study emphasize the importance of supportive policies, investment in educational technology and collaboration between the government, educational institutions and communities. With these measures, inclusive education can be implemented effectively, providing widespread benefits for all students and helping to build a more just and inclusive society.